Designing a deprivation payment for general practitioners: the UPA(8) wonderland. Issue 6773 (16th February 1991) - Carr-Hill, R A; Sheldon, T
Abstract : OBJECTIVE--To analyse critically the deprived area payment introduced in the new general practitioner contract. The payment formula is based on the Jarman underprivileged area index (UPA(8)) and aims at compensating general practitioners for increases in workload. DESIGN--Evaluation of the deprived area payment against the stated policy objective with a set of criteria for developing resource allocation formulas. MAIN OUTCOME MEASURES--The degree to which the components of the Jarman index predict the workload of general practitioners; whether construction of the index is sensible and comprehensible; and how the formula incorporates the index and is likely to work in practice. RESULTS--The fact that the index relies on census data and the way the weighting was derived means that the formula will not accurately reflect the workload. The use of statistical transformations obscures the original policy intent. There has been no validation to support the application of the index as part of a national policy. The payments are not linked to the quality of service provided and may have the perverse effect of increasing list size. CONCLUSION--The formula used as the basis of the deprived area payments is poorly suited to the policy objective of compensating general practitioners for increases in workload. More research is urgently needed to enable the effect of the payment to be monitored and a more empirically sound set of incentives to be developed.